Government debt and banking fragility: The spreading of strategic uncertainty - Russell W. Cooper; Kalin Nikolov (European Central Bank (ECB), 2018)
This paper studies the interaction of government debt and financial markets. This interaction, termed a "diabolic loop", is driven by government choice to bail out banks and the resulting incentives for banks to hold government debt rather than self-insure through equity buffers. We highlight the role of bank equity issuance in determining whether the "diabolic loop" is a Nash Equilibrium of the interaction between banks and the government. When equity is issued, no diabolic loop exists. In equilibrium, banks' rational expectations of a bailout ensure that no equity is issued and the sovereign-bank loop is operative.
Keywords: G01; G28; E44; 330; Sovereign default; Sovereign-banking loop